2008
DOI: 10.2215/cjn.03480807
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Fistula Maturation Persist Despite Preoperative Vascular Mapping

Abstract: Background and objectives: Failure to mature (primary failure) of new fistulas remains a major obstacle to increasing the proportion of dialysis patients with fistulas. This failure rate is higher in women than in men, higher in older than in younger patients, and higher in forearm than in upper arm fistulas. These disparities in the frequency of failure to mature may be due in part to marginal vessels in the high-risk groups and should be reduced by routine preoperative vascular mapping.Design, setting, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
133
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 17 publications
14
133
2
2
Order By: Relevance
“…Studies have demonstrated several clinical factors contributing to AV fistula success or failure, with older age, diabetes, and their associated complications (e.g., cardiac and peripheral vascular disease) as strong predictors of failure (10)(11)(12). In the first described AV fistulas, the failure rate was 12.5% (3), but it is as high as 40% today (13,14), probably reflecting the effect of an older dialysis population with greater comorbidity.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Studies have demonstrated several clinical factors contributing to AV fistula success or failure, with older age, diabetes, and their associated complications (e.g., cardiac and peripheral vascular disease) as strong predictors of failure (10)(11)(12). In the first described AV fistulas, the failure rate was 12.5% (3), but it is as high as 40% today (13,14), probably reflecting the effect of an older dialysis population with greater comorbidity.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Answer AVF nonmaturation or early failure is associated with older age, female sex, forearm location, and cardiovascular disease (57)(58)(59)(60). In contrast, no clinical factors have been associated with early AVG failure.…”
Section: James C Harms Md (Nephrology Fellow At University Of Alabamentioning
confidence: 99%
“…In contrast, more recent studies have reported a much higher likelihood of fistula nonmaturation, ranging between 20% and 60% (11)(12)(13). Simple clinical factors (older age, female sex, black race, vascular morbidity, and forearm location) have been repeatedly associated with fistula nonmaturation (11,14,15).…”
mentioning
confidence: 98%
“…This was highlighted in a large National Institutes of Health multicenter randomized study in which 60% of fistulas created were not suitable for dialysis despite Ͼ75% with preoperative mapping (12). Nonmaturation continues to be higher in older patients, women, and forearm fistulas (12,15,17). Although some studies have demonstrated no association between vessel size and fistula maturation (18), most centers require a minimum arterial diameter of 2 mm and a minimum venous diameter of 2.5 to 3 mm (19).…”
mentioning
confidence: 99%